2011
DOI: 10.3353/omp.15.53
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosing mucoepidermoid carcinoma: specific histologic variant or nonspecific morphologic pattern?

Abstract: Sclerosing mucoepidermoid carcinoma (SMEC) has been rarely documented, and previously reported cases have suggested that this histologic variation is basically low-grade with a favorable prognosis. In an earlier report on the firstdescribed intraoral case of SMEC of intermediate grade that recurred as a nonsclerosed, high-grade tumor 13 years after the initial surgery, we presented a primary gingival tumor that occurred in a 28-year-old man as a non-ulcerated, polypoid, 2-cm mass on the retromolar pad. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Also, in many cases long term follow up data has not been published, with many cases being reported with no recurrence or metastasis over months or less than 5 years. Only three cases report 10 or more years of follow up, one of which showed recurrence at 15 years, emphasizing the importance of long term follow up data [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, in many cases long term follow up data has not been published, with many cases being reported with no recurrence or metastasis over months or less than 5 years. Only three cases report 10 or more years of follow up, one of which showed recurrence at 15 years, emphasizing the importance of long term follow up data [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Various hypotheses suggest that it may be a response to extravasated mucin or ruptured cysts [4,8,11], due to tumour infarction [1] or caused by eosinophils [12]. The fact that some cases do not show prominent eosinophils argues against the eosinophil theory, and Ide et al [5] argue that the eosinophils are not prominent enough to cause sclerosis. It has also been suggested that the lymphoid infiltrate may occur as a reaction to ruptured cysts, and it has been postulated that similar lesions which lack this infiltrate may be older, therefore the inflammatory component has resolved [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They stated that the absence of sclerotic stroma in the recurrent case makes the etiopathogenesis of the SMEC inexplicit. They also raised the suspicion whether SMEC is a specific histologic variant or the sclerosis suggests a nonspecific morphologic pattern [8].…”
Section: Discussionmentioning
confidence: 99%
“…1 The variants include oncocytic, sclerosing, unicystic, clear cell, goblet cell, spindle cell, psammomatous and sebaceous types. 2 High grade mucoepidermoid carcinoma is characterized by the presence of more solid areas, compared to cystic areas, which are prominent in low grade. 3 Sclerosing variant of mucoepidermoid carcinoma is characterized by extensive sclerosis and paucity of cells, which can lead to misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%